Factors affecting knowledge, attitude and practices related to early childhood caries among mothers of Arabic School Children in Klang Valley, Malaysia - Mohammed, Najla'a Salameh (2016)
Introduction: Oral health of the child means more than just having good and healthy teeth. Early Childhood Caries (ECC) refers to rampant dental caries in pre-school children. It can affect the child both physically and psychologically. Many factors can affect the knowledge, attitude and practice of mothers about prevention of ECC. Objectives: To study the knowledge, attitude and practice on ECC and its associated factors among Arabic mothers of preschool and primary school children in Arabic schools that are registered in the Ministry of Education Malaysia in Klang Valley. Methodology: This was a cross sectional study conducted among 518 mothers of primary and preschool children of all Arabic schools in Klang Valley that are registered with the Ministry of Education Malaysia from December 2014 to February 2015. The mothers were chosen by using simple random sampling. Mothers that fulfilled the inclusion criteria were recruited for the study. Validated and reliable questionnaire were used in this study. Knowledge, attitude and practice were the dependent variables whereas socioeconomic characteristics, tooth care, dental fears and family factors were the independent variables. Chi-square test and binary logistic regression were used for data analysis. Results: The response rate was 87.6%. The majority of mothers were in the age group between 30 and 39 years old, living in Selangor, married, housewives, and have three to four children. The level of good knowledge on ECC among mothers from this study was 49.1%; positive attitude 46.6% and 37.8% of mothers had good practice on ECC. The predictors of good knowledge on ECC were mothers with >4 children (AOR=3.386; 95% CI: 1.779-6.447), have no fears originating from community believes (AOR=1.575; 95% CI: 1.000-2.480), have no fears of extraction (AOR=2.845; 95% CI: 1.443-5.608), and have twice daily tooth brushing habits (AOR=1.989; 95% CI: 1.266-3.126). Predictors of positive attitude were mothers with post graduate level (AOR=2.024; 95% CI: 1.287-3.184), attended infant oral health education program (AOR=2.444; 95% CI: 1.325-4.506), and good knowledge level (AOR=2.479; 95% CI: 1.600-3.843). On the other hand, having no fears originating from community believes was a protective factor of positive attitude (AOR=0.575; 95% CI: 0.369-0.896). However, predictors of good practice were mothers with >34 years old (AOR=4.403; 95% CI: 2.009-9.650), attended infant oral health education program (AOR=2.444; 95% CI: 1.085-5.506), good knowledge level (AOR=1.835; 95% CI: 1.093-3.080), and positive attitude level (AOR=4.605; 95% CI: 2.222-9.541). Conclusion: Majority of mothers‘ level of good knowledge on ECC, positive attitude towards ECC and good practice on ECC were poor. Preventive programs targeted on mothers who are 34 years old or less, have bachelor degree or less, housewives, with family income less than RM 6000, have four children or less, have not attended any infant oral health education program and have dental fears should be developed.